2020
DOI: 10.1177/0033354920946788
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dental Benefits and Use of Emergency Departments for Nontraumatic Dental Conditions in Massachusetts

Abstract: Objectives Research examining the effect of changes in Medicaid dental benefits on emergency department (ED) use for dental conditions has had mixed results. We examined the effect of changes in Medicaid dental benefits on ED use for nontraumatic dental conditions (NTDCs) among adults in Massachusetts before and after Medicaid dental benefits for adults were eliminated (July 2010) and partially restored (January 2013). Methods We used 2009-2013 data from the Massachusetts All-Payer Claims Database. The study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Each of the 53 studies met the inclusion criteria for evaluating an Adult Medicaid dental policy between 1991 and 2020 [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. Supplemental Table 1 provides a tabulated overview for all 53 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the 53 studies met the inclusion criteria for evaluating an Adult Medicaid dental policy between 1991 and 2020 [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. Supplemental Table 1 provides a tabulated overview for all 53 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing, but not eliminating Medicaid dental benefits was consistently found to increase non-traumatic dental services in emergency departments or hospitals [ 35 , 52 , 55 ]. Benefit reductions were also found to increase unmet dental needs [ 67 ].…”
Section: Conclusion From Articles Included In the Scoping Reviewmentioning
confidence: 99%
“…Although adult dental benefits are typically eliminated to reduce state spending, adult Medicaid enrollees may seek care through costlier venues after losing benefits. Studies from California and Massachusetts reported that when Medicaid adult dental benefits were eliminated, emergency department visits for nontraumatic dental conditions among adults significantly increased along with associated costs 13,14. Fewer studies have examined the indirect effects of Medicaid adult dental benefit elimination on child dental care use.…”
mentioning
confidence: 99%
“…Studies from California and Massachusetts reported that when Medicaid adult dental benefits were eliminated, emergency department visits for nontraumatic dental conditions among adults significantly increased along with associated costs. 13,14 Fewer studies have examined the indirect effects of Medicaid adult dental benefit elimination on child dental care use. Studies have found associations between parent dental benefits, parent dental care use and child dental care use.…”
mentioning
confidence: 99%